Reproductive ecology of the freshwater red alga Batrachospermum delicatulum (Batrachospermales, Rhodophyta) in three tropical streams - Necchi Jr., Orlando [UNESP]; Vis, Morgan L. (Wiley, 2005)
Batrachospermum delicatulum specimens from three stream segments were analyzed from a tropical region in south-eastern Brazil (20°18′- 20°49′S, 49°13′-49°46′W). Physical and chemical parameters and the spatial placement of thalli were investigated along with the reproductive characteristics of the gametophytic phase. Sequence data of the cox 2-3 spacer region was also utilized to evaluate genetic variation in individuals within and among stream segments. Gametophyte occurred under relatively diverse environmental conditions, whereas thalli abundance was weakly or not correlated to environmental variables within the stream segments. All specimens examined were dioecious. The ratio of male/female plants was relatively low (0.5 to 1.3) and male plants tended to occur as clumps (two or three plants together). High reproductive success was observed, as indicated by the occurrence of 100% fertilized (carposporophytic) female plants. This is similar to previous reports for this and other dioecious species, which is remarkable considering the relatively low proportion of male/female plants. Results support the two hypotheses to explain the high reproductive success in dioecious species. The occurrence of male plants in clumps was evidence for a strict spatial relationship (i.e. male plants located in upstream position of female plants in order to release spermatia, which would be carried by eddies through female plants). In contrast, the occurrence of male and female plants adjacent to each other allowed outcrossing among neighboring plants with intermingled male and female branches, which seemed more applicable to some situations (low turbulence habitats). The cox 2-3 spacer region from the 18 individuals sequenced was 376 bp and the DNA sequence was identical with no base pair substitutions. Likewise, a previous study of another Batrachospermum species showed that the same haplotypes were present in all stream segments from the same drainage basin, even though the stream segments were a considerable distance apart. Short distance dispersal either by small birds or waterway connectivity might explain these findings.
Keywords: Batrachospermum; cox 2-3 spacer; Genetic variation; Mitochondrial DNA; Population biology; Reproductive ecology; genetic variation; red alga; reproductive biology; Aves; Batrachospermales; Batrachospermum delicatulum; Rhodophyta